A God in Every Stone - Shamsie, Kamila, 1973- (London Bloomsbury, 2016)
July 1914. A young Englishwoman, Vivian Rose Spencer is running up a mountainside in an ancient land. She picks up a fig and holds it to her nose. Around her is a maze of broken columns, taller than the tallest of men. Nearby is the familiar lean form of her father's old friend, Tahsin Bey, an archaeologist. Viv is about to discover the Temple of Zeus, the call of adventure and the ecstasy of love. July, 1915. An Englishwoman and an Indian man meet on a train to Peshawar. Viv Spencer is following a cryptic message sent to her by the man she loves, from whom she has been separated by war. Qayyum Gul is returning home after losing an eye at Ypres while fighting for the British Indian army, his allegiances in tatters. When they disembark the train at Peshawar they are unaware that a connection is about to be forged between their lives - one of which they will be unaware until fifteen years later when anti-colonial resistance, an ancient artifact and a mysterious green-eyed woman will bring them together again over seventy-two hours of heartbreak, frayed loyalties and hope.
Keywords: Man-woman relationships -- Turkey -- Archaeology